The dose-response relationship between pseudoephedrine ingestion and exercise performance - Pritchard-Peschek, K. R.; Jenkins, D. G.; Osborne, M. A.; Slater, G. J.; Taaffe, D. R. (Journal of Science and Medicine in Sport, 2014)
Objectives: The purpose of the present study was to examine a possible dose-response between pre-exercise pseudoephedrine intake and cycling time trial performance. Design: Randomised, double-blind, crossover trial. Methods: Ten trained male endurance cyclists (26.5 ± 6.2 years, 75.1 ± 5.9 kg, 70.6 ± 6.8 mL kg-1 min-1) undertook three cycling time trials in which a fixed amount of work (7 kJ kg-1 body mass) was completed in the shortest possible time. Sixty minutes before the start of exercise, subjects orally ingested either 2.3 mg kg-1 or 2.8 mg kg-1 body mass of pseudoephedrine or a placebo in a randomised and double-blind manner. Venous blood was sampled at baseline, pre- and post-warm up and post-exercise for the analysis of pH and lactate and glucose concentrations; plasma catecholamine and pseudoephedrine concentrations were measured at all times except post-warm up. Results: Cycling time trial performance (?30 min) was not enhanced by pseudoephedrine ingestion. Plasma pseudoephedrine concentration increased from pre-warm up to post-exercise in both treatment conditions, with the 2.8 mg kg-1 body mass dose producing the highest concentration at both time points (2.8 mg kg-1 > 2.3 mg kg-1 > placebo; p < 0.001). Conclusions: There was large individual variation in plasma pseudoephedrine concentration between subjects following pseudoephedrine administration. A number of factors clearly influence the uptake and appearance of pseudoephedrine in the blood and these are not yet fully understood. Combined with subsequent differences in plasma pseudoephedrine between individuals, this may partially explain the present findings and also the inconsistencies in performance following pseudoephedrine administration in previous studies.